The Capability of Utilizing Abiotic Enantiomers of Amino Acids by Halomonas sp. LMO_D1 Derived From the Mariana Trench - Wang, Xiangyu; Yang, Yi; Lv, Yongxin; Xiao, Xiang; Zhao, Weishu (Frontiers in Astronomy and Space Sciences, 2021)
D-amino acids (D-AAs) have been produced both in organisms and in environments via biotic or abiotic processes. However, the existence of these organic materials and associated microbial degradation activity has not been previously investigated in subduction zones where tectonic activities result in the release of hydrothermal organic matter. Here, we isolated the bacterium Halomonas sp. LMO_D1 from a sample obtained from the Mariana Trench, and we determined that this isolate utilized 13 different D-AAs (D-Ala, D-Glu, D-Asp, D-Ser, D-Leu, D-Val, D-Tyr, D-Gln, D-Asn, D-Pro, D-Arg, D-Phe, and D-Ile) in the laboratory and could grow on D-AAs under high hydrostatic pressure (HHP). Moreover, the metabolism of L-AAs was more severely impaired under HHP conditions compared to that of their enantiomers. The essential function gene (Chr_2344) required for D-AA catabolism in strain LMO_D1 was identified and confirmed according to the fosmid library method used on the D-AAs plate. The encoded enzyme of this gene (DAADH_2344) was identified as D-amino acid dehydrogenase (DAADH), and this gene product supports the catabolism of a broad range of D-AAs. The ubiquitous distribution of DAADHs within the Mariana Trench sediments suggests that microorganisms that utilize D-AAs are common within these sediments. Our findings provide novel insights into the microbial potential for utilizing abiotic enantiomers of amino acids within the subduction zone of the Mariana Trench under HHP, and our results provide an instructive significance for understanding these abiotic enantiomers and allow for insights regarding how organisms within extraterrestrial HHP environments can potentially cope with toxic D-AAs.